2017
DOI: 10.1016/j.tsf.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Defect growth in multilayer chromium nitride/niobium nitride coatings produced by combined high power impulse magnetron sputtering and unbalance magnetron sputtering technique

Abstract: Defect growth in multilayer chromium nitride/niobium nitride coatings produced by combined high power impulse magnetron sputtering and unbalance magnetron sputtering technique. Thin Solid Films, 636, 558-566.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The images of the coating surfaces (130 µm × 90 µm) were captured using a digital camera attached with the microscope. The defect density was then quantified from binary pictures of the coatings [16]. This study was conducted to determine the effect of the chamber pressure on defect formation.…”
Section: Crystal Structure Study (Xrd)mentioning
confidence: 99%
See 4 more Smart Citations
“…The images of the coating surfaces (130 µm × 90 µm) were captured using a digital camera attached with the microscope. The defect density was then quantified from binary pictures of the coatings [16]. This study was conducted to determine the effect of the chamber pressure on defect formation.…”
Section: Crystal Structure Study (Xrd)mentioning
confidence: 99%
“…Detailed study about these defects can be found elsewhere [16,41]. The relationship of defect density (percentage of area covered by defects) with the chamber pressure is shown in Fig.…”
Section: Microstructural Study Of Coating Defectsmentioning
confidence: 99%
See 3 more Smart Citations